Age, Hf isotope and trace element signatures of detrital zircons in the Mesoproterozoic Eriksfjord sandstone, southern Greenland:are detrital zircons reliable guides to sedimentary provenance and timing of deposition? - Andersen, Tom (Geological Magazine, 2013)
The Gardar Rift in southern Greenland developed within Palaeoproterozoic rocks of the Ketilidian orogen, near its boundary with the Archaean craton. The Eriksfjord Formation was deposited at c. 1.3 Ga on a basement of c. 1.8 Ga Julianehåb I-type granite. Detrital zircons from the lower sandstone units shows a range of ages and ÎHf compatible with proto sources within the Archaean craton and the Nagssugtoquidian mobile belt north and east of the craton; zircons that can be attributed to juvenile Ketilidian sources are less abundant. This suggests a predominance of distant sources, probably by recycling of older and no longer preserved cover strata. A significant fraction of c. 1300 Ma zircons have ÎHf between 0 and -38. Rather than originating from a hitherto unknown igneous body within the Gardar Rift, these are interpreted as Palaeoproterozoic to late Archaean zircons that have lost radiogenic lead during diagenesis and post-depositional thermal alteration related to Gardar magmatism. Although the sediments originate from sources within Greenland, the age and initial Hf isotope distribution of Palaeoproterozoic and Archaean zircons mimics that of granitoids from the Fennoscandian Shield. This may reflect parallel evolution and possible long-range exchange of detritus in Proterozoic supercontinent settings. The lesson to be learned is that detrital zircon age data should not be used to constrain the age of sedimentary deposition unless the post-depositional history is well understood, and that recycling of old sediments, long-range transport and parallel evolution of different continents make detrital zircons unreliable indicators of provenance.